2005
DOI: 10.1086/426602
|View full text |Cite
|
Sign up to set email alerts
|

Self‐Organization and Vegetation Collapse in Salt Marsh Ecosystems

Abstract: Complexity theory predicts that local feedback processes may strongly affect the organization of ecosystems on larger spatial scales. Whether complexity leads to increased resilience and stability or to increased vulnerability and criticality remains one of the dominant questions in ecology. We present a combined theoretical and empirical study of complex dynamics in mineralogenic salt marsh ecosystems that emerge from a positive feedback between clay accumulation and plant growth. Positive feedback induces se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
103
0

Year Published

2014
2014
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 262 publications
(119 citation statements)
references
References 56 publications
1
103
0
Order By: Relevance
“…This strip of halophytes represents the birth of a fourth marsh at Northwick Warth. As observed by van de Koppel et al (2005) and van der Wal et al (2008) from the relatively sheltered marshes they studied, and by Pedersen and Bartholdy (2007) from an exposed context, a narrow zone of unvegetated mud separated the new marsh from the bold scarp at the edge of the low marsh. In the case of the marshes of the Danish Wadden Sea, this zone, taking the form of a channel (landpriel), persists over the entire build-up of the new marsh (Jakobsen 1954;Pedersen and Bartholdy 2007).…”
Section: A Fourth Marshmentioning
confidence: 63%
See 3 more Smart Citations
“…This strip of halophytes represents the birth of a fourth marsh at Northwick Warth. As observed by van de Koppel et al (2005) and van der Wal et al (2008) from the relatively sheltered marshes they studied, and by Pedersen and Bartholdy (2007) from an exposed context, a narrow zone of unvegetated mud separated the new marsh from the bold scarp at the edge of the low marsh. In the case of the marshes of the Danish Wadden Sea, this zone, taking the form of a channel (landpriel), persists over the entire build-up of the new marsh (Jakobsen 1954;Pedersen and Bartholdy 2007).…”
Section: A Fourth Marshmentioning
confidence: 63%
“…The Aust-Northwick marshes exhibit many features expected of autocyclic marshes (Gao and Collins 1997;van de Koppel et al 2005) and observed from marshes claimed as autocyclic, but also give evidence for a degree of external control (Table 1). Could the Severn Estuary marshes be autocyclic but with the autocyclicity substantially locked into the pattern of extrinsic factors?…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…Cordgrass modifies water flow and increases the deposition of sediments and the accumulation of peat substrate (Redfield 1972). Through this building process and scale-dependent interactions between vegetation growth, substrate building, and water flow, the developing marsh vegetation can generate hummocks (Bouma et al , 2009van de Koppel & Crain 2006), elevation gradients, and other landscape features (van de Koppel et al 2005b), which contrasts with the previous assumption that vegetation zonation is simply a product of elevation gradients (and associated local variations in abiotic and biotic drivers). Over time, however, this process can lead to the marsh being overbuilt-for example, facilitative interactions can stimulate local sediment buildup, increasing the height of the marsh.…”
Section: Cordgrass and Forbs On Cobble Beaches And In Salt Marshesmentioning
confidence: 96%